Oral anticoagulants in older patients with atrial fibrillation: insights from a nationwide study. (19th May 2022) - Rasmussen, PV; Dalgaard, FD; Gislason, GH; Pallisgaard, JL; Hansen, ML
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Bayer Background: Atrial fibrillation (AF) is a predominant risk factor of ischemic stroke and prophylactic treatment with oral anticoagulants (OACs) is recommended in older patients. Advancing age increases the risk of stroke, however, ageing simultaneously increases the prevalence of bleeding risk factors such as multimorbidity, polypharmacy, frail vessels as well as the tendency to fall. As such, treatment with OACs in older frail patients is often associated with complex risk-benefit considerations. Purpose: To examine treatment patterns with OACs in older patients with AF. Methods: Using nationwide registries and databases, Danish patients > 75 years of age with a primary diagnosis of AF between 2010 and 2018 were identified. The primary event of interest was claimed prescriptions for OACs in a period of 180 days after hospital contact due to AF. Proportions of patients treated with OACs were estimated and depicted graphically. Clinical factors associated with the probability of receiving OAC treatment were identified using adjusted logistic regression models with estimates presented as Odds Ratios (OR) with 95% Confidence Intervals (95% CI). Results: A total of 40, 027 patients were included with a slight majority of women (54%). The median age was 81 years (IQR 78-86). We found that an overall 32, 235 patients (81%) were prescribed an OAC after hospital contact due to AF. Increasing age was associated with a clear tendency toward a decreased probability of receiving OAC treatment. As such, among patients aged 75 years, 85 % received OAC treatment decreasing to 68 % in patients aged 90 years. (Figure 1) Collectively during the study period, a substantial increase in the proportion of patients treated with OACs was observed. Hence, in 2011, 63 % claimed OAC prescriptions whereas this proportion increased to 92 % in 2018. (Figure 2) Factors related to a low probability of OAC treatment were bleeding risk factors such as a history of bleeding (OR 0.58, 95% CI 0.53-0.82), hemorrhagic stroke (OR 0.21, 95% CI 0.16-0.27), treatment with dual antiplatelet therapy (OR 0.52, 95% CI 0.47-0.59) as well as markers of frailty such as osteoporosis (OR 0.78, 95% CI 0.71-0.85) and previous falling (OR 0.56, 95 % CI 0.51-0.62). Conclusions: In this large nationwide study, we found that in older patients with AF, the overall rates of OAC prescription were relatively high ( 80%) but decreased notably with age. Factors associated with not receiving guideline directed OAC treatment were generally related to bleeding risk factors or frailty. These data highlight a clinical conundrum as older patients potentially benefit the most from treatment with OACs. Figure legend Figure 1 Combined plot depicting the absolute number of patients by age (red bars) as well as the proportion of patients treated with oral anticoagulants by age (blue curve). Figure 2 Plot depicting the proportion of patients receiving treatment with oral anticoagulants by calendar year.